(untitled) (Academicia Globe: Inderscience Research, 2023)
The Turkestan General Governor is an administrative-territorial unit formed by the decree of the Russian Emperor Alexander II on the territory of Western Turkestan occupied by the Russian Empire (July 11, 1867). In the same year, the Turkestan military district was formed. Adjutant General Konstantin Petrovich von Kaufman, a close official of the Russian Tsar, was appointed the first Governor General of Turkestan. For 14 years (1867-1881) he strictly controlled the Turkestan region. Von Kaufmann, who proved to be an experienced administrator and a skilled politician in suppressing liberation movements in the Caucasus and the Baltic countries, was hailed as the "Founder of Turkestan". At a meeting of representatives of the public in Tashkent (January 22, 1868), he first called the Russians the "elder brother" of the Turkestan peoples. By the time of the conquest of Turkestan by Russia, there existed a rather harmonious system of education created by the Muslim clergy, firmly based on the rules of the Koran and Sharia, brightly colored by fanaticism and religious intolerance. There were two types of religious schools: schools and madrasahs. Schools served as primary education, and madrasas provided secondary and higher education.